(untitled) (Ciudades, 2025)
Urban design in the second half of the 20th century has developed according to social, cultural and economic factors and demands. Thus, mixed development arose in response to a wide demand for typological variety, where the single-family housing would be one of these typologies to be integrated and combined with others in the form of collective housing. The process experienced in Huesca is analysed, starting with a clear typological separation, followed by actions with the addition of areas according typologies, and ending with projects that achieve the maximum integration of single-family housing with a true mixture within the urban design.